High‐resolution deep functional imaging of the whole mouse brain by photoacoustic computed tomography in vivo. Issue 1 (21st June 2017) - Zhang, Pengfei; Li, Lei; Lin, Li; Hu, Peng; Shi, Junhui; He, Yun; Zhu, Liren; Zhou, Yong; Wang, Lihong V.
Abstract: Photoacoustic computed tomography (PACT) is a non‐invasive imaging technique offering high contrast, high resolution, and deep penetration in biological tissues. We report a PACT system equipped with a high frequency linear transducer array for mapping the microvascular network of a whole mouse brain with the skull intact and studying its hemodynamic activities. The linear array was scanned in the coronal plane to collect data from different angles, and full‐view images were synthesized from the limited‐view images in which vessels were only partially revealed. We investigated spontaneous neural activities in the deep brain by monitoring the concentration of hemoglobin in the blood vessels and observed strong interhemispherical correlations between several chosen functional regions, both in the cortical layer and in the deep regions. We also studied neural activities during an epileptic seizure and observed the epileptic wave spreading around the injection site and the wave propagating in the opposite hemisphere. Abstract : Aim and scope: To reveal the mechanism of brain disorders, an imaging methodology with increased spatial and temporal resolution as well as deep penetration in tissues is highly required. We report a photoacoustic computed tomography (PACT) system for mapping the microvascular network of a whole mouse brain with the skull intact. We then performed functional imaging and observed strong interhemispherical correlations between functional regions and the epileptic wave propagating in the deep brain.